Sustainable Cloud Data Centers: A survey of enabling techniques and technologies - Shuja, Junaid; Gani, Abdullah; Shamshirband, Shahaboddin; Ahmad, Raja Wasim; Bilal, Kashif (Renewable & sustainable energy reviews, 2016)
Cloud computing services have gained tremendous popularity and widespread adoption due to their flexible and on-demand nature. Cloud computing services are hosted in Cloud Data Centers (CDC) that deploy thousands of computation, storage, and communication devices leading to high energy utilization and carbon emissions. Renewable energy resources replace fossil fuels based grid energy to effectively reduce carbon emissions of CDCs. Moreover, waste heat generated from electronic components can be utilized in absorption based cooling systems to offset cooling costs of data centers. However, data centers need to be located at ideal geographical locations to reap benefits of renewable energy and waste heat recovery options. Modular Data Centers (MDC) can enable energy as a location paradigm due to their shippable nature. Moreover, workload can be transferred between intelligently placed geographically dispersed data centers to utilize renewable energy available elsewhere with virtual machine migration techniques. However, adoption of aforementioned sustainability techniques and technologies opens new challenges, such as, intermittency of power supply from renewable resources and higher capital costs. In this paper, we examine sustainable CDCs from various aspects to survey the enabling techniques and technologies. We present case studies from both academia and industry that demonstrate favorable results for sustainability measures in CDCs. Moreover, we discuss state-of-the-art research in sustainable CDCs. Furthermore, we debate the integration challenges and open research issues to sustainable CDCs.